The Narrators who were Mentioned by Al-Dahabi in his Book Al-Kashif (Youjhal): A Critical Study (Islamic Sciences Journal, 2023)
This paper: the narrators whom Al-Dhahabi said in Al-Kashef (ignoring them) a critical study), contains the study of a group of (13) narrators who studied the life of Imam Al-Dhahabi  in brief, in terms of his name, ancestry, surname, birth, death, and books, and scholars who had praised him. It also included the study of the narrators arranged according to the letters of the dictionary; the study tackles the narrators by mentioning the full name of the narrator and mentioning his surname and title, if any, as well as his description and whoever narrated it. Then the speech of Imam Al-Dhahabi about him, followed by a study of the status of that narrator with criticism  and the modification. Then the most prior and proper statement in his case is stated. The results are mentioned the main sources and references that the researcher referred to (get benefit from it in the search), and God guide to the straight path.